(untitled) (International Journal of Occupational Safety and Health, 2023)
Introduction: Auto–rickshaws are still the most commonly used mode of transportation in Tier II & III cities where metros or application-based cab aggregators are non-existent / not available. Auto-Rickshaw Drivers (ARDs) are at a higher risk for Cardiovascular Disease (CVD) because of their common lifestyle practices like irregular eating habits, sedentariness, addictions, and work-related stress. Studies have found that hypertension (HTN) is highly prevalent among ARDs in comparison to the general population. We studied the prevalence of HTN among ARDs of Belagavi. Methods: It was a cross-sectional study conducted among 600 regular ARDs operating within Belagavi City between January to December 2016. The sample size was calculated to be 570 and rounded off to 600. Two ARDs who were last in the queue were selected from 300 major auto rickshaw stands. After getting informed consent, we collected the data through personal interviews and recorded the blood pressure of all the study participants. Data were analyzed using SPSS software. The Institutional Ethics Committee of J. N. Medical College approved the study. Results: Among the 600 participants studied, 54 (09%) were previously known and 228 (38%) were newly diagnosed hypertensive. HTN was significantly associated with age, religion, educational status, length of working hours, years in present occupation, and body mass index. Conclusion: The prevalence of HTN was high compared to the general adult population and increased with increasing age, length of working hours, years in present occupation, and body mass index.